Implementasi Model Diagnostik Tes Kesulitan Siswa Pasca Pandemi Covid-19 - Gaffar, Aden Arif; Susilo, Sigit Febrianto; Nurmalawaty , Nabilla; Robi’ah, Nia Naimatul (Papanda Publisher, 2024)
The Covid-19 pandemic has significantly affected education worldwide, including in Indonesia. The sudden transition from face-to-face to online learning created various learning difficulties, ranging from cognitive and technical to psychosocial challenges. This literature review aims to analyze the implementation of diagnostic tests as a strategy to identify and overcome students’ learning difficulties after the pandemic. The review covers national and international studies published between 2020 and 2024. Findings indicate that diagnostic tests are effective in detecting learning loss, specific weaknesses, and provide a solid foundation for designing more targeted remedial strategies. However, implementation still faces challenges such as limited resources, teachers’ diagnostic competence, and policy support. This review emphasizes the need to integrate diagnostic assessment into the national education system and to strengthen teacher capacity.